Selected Questions Regarding Hedge Funds - Schich, Sebastian (OECD Publishing, 2007)
There has been rapid growth in the share of assets under control of hedge funds over the past decade and, as a result, these entities have now become firmly entrenched in the universe of investment vehicles and, in turn, have themselves become important investors. Against this background, the OECD Committee on Financial Markets (CMF) discussed specific issues related to these entities on several occasions as part of its market surveillance activity. The present article provides a summary of selected aspects of recent CMF discussions related to hedge funds, focusing in particular on the responses to a questionnaire on hedge funds that was circulated prior to the CMF meeting in May 2007 to inform the discussion at that meeting. These various discussions suggested that a consensus is emerging that the most efficient way to address any policy concerns related to the activity of hedge funds is to focus on hedge fund investors and counterparties rather than on these entities themselves. Only a minority of countries are considering policy actions in a variety of areas, but many respondents seem to underline the need for public authorities to continue monitoring developments regarding hedge funds
Keywords: Finance and Investment